Program Penghijauan sebagai Solusi Pemanfaatan Lahan Tidak Produktif di Desa Sidomukti, Motoduto, dan Talumopatu - Tangio, Julhim S; Husain, Rustam I.; Laliyo, Lukman Abdul Rauf; Mohamad, Erni; Bialangi, Nurhayati; Kilo, Ahmad Kadir (Universitas Negeri Gorontalo, 2025)
This community service program aims to address the issue of unproductive land in three villages—Talumopatu, Sidomukti, and Motoduto—in Gorontalo Province by implementing sustainable land management practices. The program focused on soil conservation, organic farming, and polyculture techniques to rehabilitate degraded land, reduce erosion, and improve soil fertility. The initiative included training and workshops for local farmers to promote the adoption of environmentally friendly agricultural practices. Throughout the program, community participation was high, and significant progress was made in transforming underutilized land into productive green spaces. The project also emphasized the importance of crop diversity in preventing soil degradation. The results indicate that the program successfully improved land productivity, enhanced environmental awareness, and empowered local farmers with sustainable farming skills. The success of this program opens opportunities for similar initiatives in other regions facing environmental challenges.